Primeval new world Disc 2 - Reeves-Stevens, Judith; Wood, Martin; Matter, Niall; Canning, Sara, 1987-; Rahim, Danny; Omni Film Productions; Anomaly Productions, LTD.; Entertainment One (Firm) ([United States] : Anomaly Productions, LTD., 2012)
Evan Cross, a wealthy and brilliant innovator, leads a diverse team that operates from a secret and cutting edge headquarters, named the Tank. From this precinct, the team operates a top-secret warning system that allows them to find anomalies and track prehistoric creatures that come through. Now the race is on to find the creatures before they find the unsuspecting public.
Clean up on aisle three -- Babes in the woods -- Truth -- Breakthrough.
Title from container.
Bonus: Behind-the-scenes featurettes.
Director of photography, Michael C. Blundell, Ryan McMaster ; editors, Gordon Rempel, Brad Rines, Ron E. Yoshida ; music composer, Andrew Lockington.
Niall Matter, Sara Canning, Danny Rahim.
Rating: TV14.
DVD, 16x9 (1.78:1) widescreen; 5.1 Dolby Digital.
Keywords: Civilization -- Protection -- Drama; Animals, Fossil -- Drama; Curiosities and wonders -- Drama; Action and adventure television programs; Video recordings for the hearing impaired